Transversality by text-messaging, co- creating skateboards and using a destabilising grammar in writing - Aronsson, Lena (Murmurations: Journal of Transformative Systemic Practice, 2018)
Starting from Deleuze and Guattari’s remark that concepts are unstable and moving assemblages of components, producing rather than representing, this article asks what the concept of transversal/-ity might be and do. The question originated from a doctoral course on Deleuzian research methodologies and transversal writing, and is basically the way I, as a confused first-year doctoral student, tried to grasp the concept. In this paper, I return to and reuse my notes from the course and a text message conversation with a colleague in which we experimented with the transversality concept in order to compose a meaningful account. By putting to work a grammatical investigation of the concept of transversality, I ask what it is, what it can be, and what it will do. Guided by a destabilising grammar, the possible practices of transversality are unfolded from the co-constitution of my notes and various texts, events, and phenomena. Finally, I reflect upon the usefulness of this exercise, in relation to the aim of composing a meaningful account and the obligation to justify scientific knowledge production. These practices of destabilising by grammar, connecting texts and experiences, and reflecting on meaning-making are both the methodology of the paper and, at the same time, the result. Hence, research processes can sometimes be vague and uncertain, but still worth a try. Abstrakt (Swedish) Med utgångspunkt i Deleuze och Guattaris påpekande att begrepp är instabila och rörliga sammansättningar av komponenter, producerande snarare än representerande, frågar den här artikeln vad begreppet transversal/-itet kan vara och göra. Frågan har sitt ursprung i en doktorandkurs om Deleuziska forskningsmetoder och transversalt skrivande, och är i grund och botten det sätt på vilket jag som förvirrad första-års-doktorand försökte förstå begreppet. I denna artikel återvänder jag till, och återanvänder, mina anteckningar från kursen och en sms-konversation med en kollega, där vi experimenterade med transversalitetsbegreppet för att skapa en meningsfull förståelse. Genom att göra en grammatisk undersökning av begreppet transversalitet kan jag fråga vad det är, vad det kan vara och vad det ska göra. Vägledd av en destabiliserande grammatik kommer möjliga transversalitetspraktiker att vecklas ut från sammanflätningen av mina anteckningar och olika texter, händelser och fenomen. Slutligen kommer jag att reflektera över användbarheten av denna övning i förhållande till avsikten att skapa en meningsfull förståelse och skyldigheten att motivera den vetenskapliga kunskapsproduktionen. Dessa praktiker av att destabilisera genom grammatik, koppla samman texter och erfarenheter och reflektera över meningsskapande är både artikelns metodik och samtidigt resultatet. Ibland kan forskningsprocesser således vara vaga och osäkra, men ändå värda ett försök.